FEATURES OF THE FORMATION OF PRODUCTIVITY AND ADAPTIVE REACTIONS IN LEGUMINOUS CROP VARIETIES WITH RECESSIVE ALLELES OF GENES - S. N. Agarkova; N. E. Novikova; R. V. Belyaeva; E. V. Golovina; Zh. A. Belyaeva; Z. R. Tsukanova; N. I. Mit’kina (Труды по прикладной ботанике, генетике и селекции)
Researches were carried out on varieties, hybrids, isogenic lines and mutants of peas of various use developed from the beginning of the 1980s up to 2013. Experimental material was investigated under field conditions in the collection, hybridization and breeding nurseries as well as in the process of competitive variety testing in Orel Province. It is shown that one or several recessive alleles of the genes introduced into the genotypes of new varieties of grain, fodder and vegetable peas, blue lupin and soybean can influence the changees in a great number of morphological and physiological parameters determining plant growth, development and also characteristics in the system of yield formation. Reduction of leaf area in leafless pea varieties and lupin varietitts with limited branching is connected with the weakening of root system growth, which is caused by trophic interaction between these organs.